Bushen Huoxue decoction alleviates bisphenol a-induced infertility through the PMK-1 mitogen-activated protein kinases signaling pathway and downstream mitochondrial unfolded protein response in Caenorhabditis elegans - Chen, Linlin; Wu, Kanglu; Shou, Chenyi; Zhang, Lijun; Tu, Mengya; Wang, Borui; Cai, Yun; Zheng, Zihui; Sun, Jia; Ruan, Qinli; Guo, Jun (Frontiers in Pharmacology, 2026)
IntroductionBushen Huoxue (BSHX) decoction is a traditional Chinese medicine formula that has been utilized clinically to treat Diminished Ovarian Reserve. However, the underlying mechanisms by which BSHX decoction increases fertility from the perspective of systemic stress protective responses remain poorly understood. This study aims to investigate how BSHX decoction improves female fertility by improving systemic stress resistance in a fertility-defective Caenorhabditis elegans model.MethodsBisphenol A (BPA) was utilized to create a fertility-defective C. elegans model. Brood size was used to evaluate fertility. Survival under heat stress was used to evaluate stress resistance. Loss-of-function mutants and fluorescent protein transgenic strains were used to evaluate gene function. Polymerase chain reaction and RNA interference were used to detect gene expression levels or protein function.Results and DiscussionBSHX decoction significantly increased the fertility of BPA-exposed nematodes by inhibiting the accumulation of RHO-1 proteins in proximal oocytes. BSHX enhanced the heat stress resistance of germ cells, which is mediated by the PMK-1 and JNK mitogen-activated protein kinases (MAPK) pathways in germ cells. BSHX upregulated the transcriptional level and fluorescent protein level of the innate peptide T24B8.5 via the PMK-1 MAPK pathway. PMK-1 MAPK, induced by BSHX, further activated the mitochondrial unfolded protein response (UPRmt) in the gonad and intestine. The UPRmt -regulated gene hsp-6 was required to maintain mitochondrial function by reducing mitochondrial ROS levels and elevating the mitochondrial membrane potential, ultimately increasing the female fertility. In addition, a combination of metabolites (salvianolic acid B, quercetin, and asperosaponin VI), derived from the BSHX decoction, significantly enhanced the fertility of BPA-exposed nematodes through a mechanism highly similar to that of the BSHX decoction. Therefore, BSHX decoction increases fertility through the PMK-1 MAPK pathway and hsp-6-mediated UPRmt in BPA-exposed C. elegans.